Hermenêutica da facticidade e coexistência cotidiana com outros: Heidegger e a Retórica de Aristóteles - Guerche, Ronaldo Palma (2011)
The present study has the objective of presenting the reconstruction of Heidegger's interpretation of Aristotle's Rhetoric in the period between 1922 and 1927 in the context of hermeneutics of facticity project. The starting point is the statement found in Being and Time that the Rhetoric of Aristotle should be understood as the hermeneutics of being there in everyday interaction with others. Considering that this statement was not developed in Being and Time, is take as the basis for developing this theme the interpretation of Aristotle's Rhetoric in the Heidegger's course Basics Concepts of Aristotelian Philosophy.